1993
DOI: 10.1093/oxfordjournals.pubmed.a042822
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and pregnancy: an international comparison

Abstract: A study was set up to compare the drinking habits of women of childbearing age in two cities (Milan and Southampton) in two countries, Italy and the United Kingdom, and to look at the effects of alcohol consumption on the weight of the babies born to these women. The sample consisted of 1516 women in Milan and 996 in Southampton, who were interviewed after delivery; data on their drinking history, before and during pregnancy, were gathered, together with social, demographic and health data. The clinical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Overall, maternal drinking was not associated with lower birth weight, but the authors concluded that birth weight is affected only by abusive drinking (Bonati and Fellin, 1991), the small proportion who drank between meals. Primatesta et al (1993) also reported low rates of binge drinking (1.4%) among prepregnant women in Milan. However, in this same study, 9% of the women reported risky to very risky average weekly consumption of alcohol, with 29% continuing to drink daily during pregnancy.…”
Section: Relevant Literature On Fasd and Maternal Drinking In Italymentioning
confidence: 89%
See 2 more Smart Citations
“…Overall, maternal drinking was not associated with lower birth weight, but the authors concluded that birth weight is affected only by abusive drinking (Bonati and Fellin, 1991), the small proportion who drank between meals. Primatesta et al (1993) also reported low rates of binge drinking (1.4%) among prepregnant women in Milan. However, in this same study, 9% of the women reported risky to very risky average weekly consumption of alcohol, with 29% continuing to drink daily during pregnancy.…”
Section: Relevant Literature On Fasd and Maternal Drinking In Italymentioning
confidence: 89%
“…In Italy, where daily, moderate drinking is believed to be the predominant pattern, some studies have shown no relationship between maternal alcohol consumption, reduced birth weight, or pregnancy loss (De Nigris et al, 1981;Parazzini et al, 1994Parazzini et al, , 1996Primatesta et al, 1993). Other studies, however, have linked prenatal alcohol use and smoking with low birth weight.…”
Section: Relevant Literature On Fasd and Maternal Drinking In Italymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Abel (1996), the increases in birth weight in epidemiological studies related to moderate drinking during pregnancy (Mills et al, 1984;Lumley et al, 1985;Kline et al, 1987;Little and Wendt, 1991;Godel et al, 1992;Larroque et al, 1993;Lazzaroni et al, 1993;Primatesta et al, 1993) have received little attention. In contrast to the human studies where the increase in body weight, even though slight-tomodest, is not uncommon, it has been rarely reported in animal studies.…”
Section: Effects On Birth Weightmentioning
confidence: 99%
“…While descriptions of fetal alcohol syndrome (FAS) existed in the Italian literature (Calvani et al, 1985; Moretti and Montali, 1982; Roccella and Testa, 2003; Scianaro et al, 1978; Scotto et al, 1993), early maternal risk studies found little relationship between maternal alcohol use and adverse outcomes (de Nigris et al, 1981; Parazzini et al, 1994, 1996; Primatesta et al, 1993). Prenatal alcohol use and smoking were linked with low birth weight (Lazzaroni et al, 1993); one-third of women delivering in Italian hospitals were daily drinkers, even after recognition of pregnancy (Bonati and Fellin, 1991); and “abusive” and binge drinking were occasionally linked to spontaneous abortion and low birth weight (Cavallo et al, 1995).…”
Section: Introductionmentioning
confidence: 99%